(untitled) (Journal of Imam Al-Kadhim College, 2024)
The phenomenon of domestic violence is a negative phenomenon which began to spread in our societies and in abundance because it is based on a basic idea no matter how different its definitions of force, violence and hatred generated among the members of the same family whether this hatred has physical or psychological foundations or arising from the distinction between individuals practiced by the father Or the mother or among the rest of the family or may be poverty and destitution is Sieh, there were different reasons that lead to the aggravation of this phenomenon As this phenomenon began to increase, it is necessary to accelerate the search for solutions to it, through which we can try to reduce this phenomenon or eliminate it by not bad. This is done by laying the foundations of punishment and appropriate punishment on all those who commit it through enacting legislation relating to this phenomenon and spreading awareness and culture of awareness to limit it through social networking sites and through television channels and radio stations. It is also possible to spread this culture through religious platforms, and to indicate the type of punishment to be committed, through these means we can seek to reduce this phenomenon